ISLAMIC REPRESENTATION: THE CULTURE OF EDUCATION IN FINLAND PERSPECTIVE OF BUYA HAMKA - maulaya, Rosendah Dwi; Alamin, Nurul Salis; Susanti, Cela Petty; Avilya, Annisa (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2024)
Finland's educational culture is indeed quite unique. There are no minimum passing criteria. Finnish education has a focal point on character education and problem-solving skills. Not much different from the Finnish education system which looks perfect, the figure of Indonesian cleric Buya Hamka carries almost the same pillar of education. Based on Sufism, akhlaqy with the aim of forming commendable reason / behavior in students. The purpose of this study is to find the correlation of Finnish education in the lens of Islamic education from the perspective of Buya Hamka. The research method used is the Systematic Literature Review (SLR) method. The findings obtained are the concept of Finnish education oriented towards the development of superior personal character of students. The application of education seeks a minimum of conditions and criteria that will bind and curb students' freedom of exploration. The reflection of Finnish education in the perspective of Buya Hamka lies in the principle of character building. According to Hamka in his Sufism studies, humans have three universal cores, namely the intellect, heart, and five senses. By maximizing the three based on nature, it will form a superior human person with the virtue of reason. There are three things that must be passed through in order to achieve the virtue of reason: through character, through study, and through experience. Education through the experience of Buya Hamka's perspective is realized in the form of project-based learning in Finland. The learning will provide an output of student character that is active and never gives up. Thus Finnish educational culture has the same roots as Buya Hamka's concept of education, although the substance of the material is different.